Pengaruh Intellectual Capital, CSR, dan GCG terhadap Kinerja Keuangan Perusahaan Manufaktur yang Terdaftar di BEI Periode 2015-2019 - Erni Dwijayanti; Risal Rinofah; Pristin Prima Sari (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
The purpose of this study is to determine the influence of Intellectual Capital, Corporate Social Responsibility (CSR), and Good Corporate Governance (GCG) on financial performance in manufacturing companies listed on the IDX for the period 2015-2019. The variables used in this study are intellectual capital, corporate social responsibility (CSR), and good corporate governance (GCG) variables as dependent variables, while dependent variables are financial performance. This type of research is descriptive research with a quantitative approach. The subject of this study is a manufacturing company registered with the IDX for the period 2015-2019. Secondary data is obtained from the annual report of 9 companies with purposive sampling. Then the data is analyzed using multiple linear regression techniques. The results of the study with the t test showed that the variable Intellectual Capital (X1) had no significant effect on financial performance (Y) with a significance value of 0.169 > 0.05; Corporate Social Responsibility (X2) variables have a significant effect on financial performance (Y) with a significance value of 0.003 < 0.05; The Good Coporate Government (X3) variable has a significant effect on financial performance (Y) with a significance value of 0.026 < 0.05. Keywords: Intellectual Capital; Corporate Social Responsibility; Good Corporate Governance; Financial Performance